IMPROVING PRODUCT MANUFACTURING EFFICIENCY BY ENHANCING THE WORKING PARTS OF SORTING ROBOT MANIPULATORS - A. O. Yoqubjanov; Sh. T. Toshqulov (Web of Journals Publishing, 2024)
This article delves into methods to enhance product manufacturing efficiency by refining the working parts of sorting robot manipulators in industrial processes. It highlights the role of robotic technologies, particularly manipulators, in boosting both efficiency and product quality in manufacturing. The study investigates key technological attributes of these robot manipulators, exploring ways to augment their operational performance and precision.
Keywords: robot manipulator, sorting, efficiency, automation, optimization, manufacturing, artificial intelligence, productivity, industrial robots